The Haliburton primer - Haliburton, M. W. (Margaret Winifred), 1855-1928; Payne, Bruce Ryburn, 1874-1937; Burd, C. M. (Clara Miller), 1873-1933 (Salt Lake City, UT : Project Gutenberg, 2022)
"The Haliburton Primer" by M. W. Haliburton is an educational publication aimed at teaching young children how to read, likely written in the early 20th century. This primer combines engaging stories about children with pedagogical techniques to improve reading skills, focusing on vocabulary and phonics in a playful manner. The likely topic of the book revolves around foundational literacy methods suitable for classroom settings. The content primarily consists of simple stories and actions featuring characters such as Frank, Alice, and Grace, who engage in playful activities like running, jumping, and playing with toys. Each section introduces new vocabulary words and phonetic sounds through structured sentences and rhythmic "phonic jingles," encouraging phonemic awareness while keeping young readers engaged. The interactions among the children not only help lay the foundation for reading comprehension but also foster a love for language through rhyme and song. The Primer is designed to assist teachers in creating an effective reading program for early learners, blending instruction with enjoyable reading practices. (This is an automatically generated summary.)
Release date is 2022-09-30
Charlene Taylor, judeeylander and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Readers (Primary)